2014
DOI: 10.19261/cjm.2014.09(2).12
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Control of Molecular Configuration Instability via Vibronic Coupling. Pseudo Jahn-Teller Stabilization of Vertically Excited States of F2CO, N2H2 and H2C2O Molecules

Abstract: Abstract. The pseudo Jahn-Teller effect is employed to explain the origin of distortions of carbonyl fl uoride, diazene and ketene molecules in the lowest singlet and triplet excited states. The ground state and the excited electronic states of considered molecules were calculated by ab initio SCF CI method with the use of the 631G-type basis set. The corresponding pseudo Jahn-Teller coupling constants are estimated by fi tting the ab initio data for the adiabatic potential curves of the molecules to the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…16 Electron scattering by ketene has been studied by computational methods using the R-matrix method for energies ranging from 0 to 10 eV, 17 and the calculated vertical excitation energies of the first two excited states are in good agreement with experimental results. The electron scattering calculations predict two π* shape resonant states, one core-excited shape resonant state and one Feshbach resonant state.…”
Section: Structure Bonding and Spectroscopymentioning
confidence: 59%
“…16 Electron scattering by ketene has been studied by computational methods using the R-matrix method for energies ranging from 0 to 10 eV, 17 and the calculated vertical excitation energies of the first two excited states are in good agreement with experimental results. The electron scattering calculations predict two π* shape resonant states, one core-excited shape resonant state and one Feshbach resonant state.…”
Section: Structure Bonding and Spectroscopymentioning
confidence: 59%
“…The second triplet excited 3 A 1 state is stabilized by the out-of-plane distortion to the pyramidal nuclear confi guration also of C s symmetry, but the refl ection plane in this case is perpendicular to the molecular plane of the C 2v structure (Figure 1e). Previously [19] we have shown that instability of the high-symmetry C 2v nuclear confi guration of ketene molecule in the 3 A 2 and 3 A 1 excited states and the corresponding low-symmetry in-plane and out-of-plane distortions are due to the pseudo Jahn-Teller mixing of these states with higher excited 3 B 1 state. From this statement, some conclusions can be drawn, which may be useful in the analysis of distortions of coordinated ketene molecule.…”
Section: Resultsmentioning
confidence: 93%
“…A more thorough analysis of the origin of stabilization of the vertically excited states of carbonyl fluoride molecule F2CO in its first excited singlet and triplet electronic states based on the numerical estimations of the PJTE parameters was performed in Ref. [27]. The analysis confirmed that this distortion is produced entirely by the vibronic mixing of these states with the higher excited states of appropriate symmetry.…”
Section: Introductionmentioning
confidence: 92%